Soft skills and dental education - Gonzalez, M.A.G.; Abu Kasim, N.H.; Naimie, Z. (2013)
Soft skills and hard skills are essential in the practice of dentistry. While hard skills deal with technical proficiency, soft skills relate to a personal values and interpersonal skills that determine a person's ability to fit in a particular situation. These skills contribute to the success of organisations that deal face-to-face with clients. Effective soft skills benefit the dental practice. However, the teaching of soft skills remains a challenge to dental schools. This paper discusses the different soft skills, how they are taught and assessed and the issues that need to be addressed in their teaching and assessment. The use of the module by the Faculty of Dentistry, University of Malaya for development of soft skills for institutions of higher learning introduced by the Ministry of Higher Education, Malaysia.